Business intelligence framework: a case study of Mydin Mohamed Holdings / Nur Azaliah Abu Bakar - Abu Bakar, Nur Azaliah (2004)
Business Intelligence widely used to recognize the capabilities available in the firm; state of the art, trends, future directions in the markets, technologies, regulatory environment where the firm competes; and the actions of competitors and it's implications. The purpose of this study is to come out with a framework of BI for MYDIN, besides to study the business flow in MYDIN in aligning with IT and to recognize the significance of BI to MYDIN business. The first chapter are discussing about the research's objective, scope and its benefits, achieved by closely examining the background of problem faced in MYDIN aligning with Business Intelligence concept. The significance of the Business Intelligence for MYDIN's businesses is also covered in this chapter. MYDIN's background and its retail system business model were examined to facilitate Business Intelligence solutions. An effective Business Intelligence solution in MYDIN requires identification of the business strategy, competitive forces and competitive advantage. Result of this study is cited in chapter five collectively with MYDIN's Value Chain Analysis. The design of MYDIN's Business Intelligence is discussed in chapter six, which covers the technological aspect of Business Intelligence, such as the architecture and process. Result of this study, Business Intelligence Framework, is proposed in chapter seven. The framework covers the operational, technical, economical and social aspects of MYDIN. Problems and considerations in implementing Business Intelligence Framework are also discussed in this chapter. Finally is the conclusion and suggestion of future enhancement for better Business Intelligence framework design in MYDIN. It is believed that, having guidance from this research, MYDIN are able to have a successful Business Intelligence solution, thus will assist the company to gain more profit in the future.